The Nanoworld of the Tripartite Synapse: Insights from Super-Resolution Microscopy - Heller, Janosch P.; Rusakov, Dmitri A. (Frontiers in Cellular Neuroscience, 2017)
Synaptic connections between individual nerve cells are fundamental to the process of information transfer and storage in the brain. Over the past decades a third key partner of the synaptic machinery has been unveiled: ultrathin processes of electrically passive astroglia which often surround pre- and postsynaptic structures. The recent advent of super-resolution microscopy has begun to uncover the dynamic nano-world of synapses and their astroglial environment. Here we overview and discuss the current progress in our understanding of the synaptic nano-environment, as gleaned from the imaging methods that go beyond the diffraction limit of conventional light microscopy. We argue that such methods are essential to achieve a new level of comprehension pertinent to the principles of signal integration in the brain.